Mathematical development program for calculation of fatty acid composition blend of vegetable oils - Belemets, Tatiana; Yushchenko (Gonchar), Natalia; Lobok, Alexey; Radzievska, Irina; Polonskaya, Tatiana (My University, 2016)
The method of solution of the problem of polyunsaturated fatty acids (PUFA) lack in milk products is offered in the work. It is offered to create the milk-containing products (sour cream product) with adjusted fatty acid composition. The possibility of replacement of the mass part of milk fat (50 %) by the blend of natural vegetable oils was studied.
Keywords: натуральні рослинні олії; купажування математичним методом; молоковмісні продукти; натуральные растительные масла; купажирования математическим методом; молокосодержащие продукты; natural vegetable oils; blend by mathematical method; milk-containing products; кафедра технології молока і молочних продуктів; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів; кафедра біотехнології і мікробіології; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка